Implementasi Web Scraping untuk Pengumpulan data pada website SINTA - Adila, Nelawati (Politeknik Ganesha Medan, 2022)
SINTA is a website portal pioneered by the Director General of R&D Improvement, Ministry of Research Technology, and Higher Education, Republic of Indonesia to make it easier for researchers to search for journals for publication. However, in its implementation, many researchers have encountered problems, one of which is in the form of searching for publication duration and ranking, as well as searches that are carried out manually, making it difficult for researchers to find a place to publish. In this study, the author took journal data based on the SINTA website with Web scraping techniques using the Python programming language and then stored the data in the SINTA database, then scheduling a Cron job so that the data in the database was always updated. It is hoped that the results of this study can help researchers in searching for journals for publication.